2008
DOI: 10.1016/j.juro.2008.01.068
|View full text |Cite|
|
Sign up to set email alerts
|

Best Practice Policy Statement on Urologic Surgery Antimicrobial Prophylaxis

Abstract: The recommendations provided in this document, including specific indications and agents enumerated in the Tables, can assist urologists in the appropriate use of periprocedural antimicrobial prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
449
1
26

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 752 publications
(481 citation statements)
references
References 83 publications
5
449
1
26
Order By: Relevance
“…Fluoroquinolones are recommended as the first choice for antibiotic prophylaxis in TR-PB by EAU [18] and AUA [25] guidelines, but in the last few years, the increasing resistance to fluoroquinolones has caused an alarming increase in severe infectious complications after prostate biopsy [26]. Recently, Wagenlehner et al [3] reported that fluoroquinolones were used in 98.2 % of patients, but resistance against fluoroquinolones was seen in 60 % of all bacterial strains isolated after the procedure.…”
Section: Main Findingsmentioning
confidence: 99%
“…Fluoroquinolones are recommended as the first choice for antibiotic prophylaxis in TR-PB by EAU [18] and AUA [25] guidelines, but in the last few years, the increasing resistance to fluoroquinolones has caused an alarming increase in severe infectious complications after prostate biopsy [26]. Recently, Wagenlehner et al [3] reported that fluoroquinolones were used in 98.2 % of patients, but resistance against fluoroquinolones was seen in 60 % of all bacterial strains isolated after the procedure.…”
Section: Main Findingsmentioning
confidence: 99%
“…2 To provide a Canadian perspective, the Canadian Urological Association (CUA) Guidelines Committee approached our panel to provide rigorous evidence-based guidelines on the use of antimicrobial prophylactic therapy in urologic procedures that would be applicable in Canada. We concentrated our efforts on areas unique to urology, including urinary tract manipulation, stone surgery, endoscopic surgery and transrectal biopsy of the prostate (TURP).…”
Section: Need For Guidelinesmentioning
confidence: 99%
“…Patients with large stone burden, associated pyuria, history of pyelonephritis, and adjunctive operative procedure including stent, nephrostomy insertion, PCNL or ureteroscopy are at a higher risk of developing pyelonephritis post-ESWL. 2 The choice of specific agent for prophylaxis should be based, in part, on the local epidemiology of drug resistance in potential uropathogens (Grade D, Level of Evidence IV). cua guidelines on antibiotic prophylaxis…”
Section: Guideline Recommendationsmentioning
confidence: 99%
“…It is proposed that the resistant organisms are introduced into the bladder and bloodstream from the rectum during the biopsy procedure. Since fluoroquinolones are common antibiotics administered before the procedure, patients already colonized with these resistant organisms may be at higher risk for infection (13). A logical approach to providing accurate prophylaxis is to identify the patients that are harboring the resistant bacteria by culturing rectal swabs prior to the biopsy.…”
mentioning
confidence: 99%